Measurement and evaluation of co-existing crack propagation in single-crystal superalloys in hot corrosion fatigue environments - Brooking, L.; Ferguson, C.; Mason-Flucke, Julian C.; Gibson, Grant J.; Leggett, Jonathan; Palmer, I.; Nicholls, John R.; Gray, Simon (Springer, 2021)
Gas turbines blades are required to operate at high temperatures while being subjected to stress and corrosive environments. These demanding conditions have led to the need to better understand the interactions between corrosion and loading in order to improve lifing algorithms used for service interval predictions. A new crack growth measurement technique involving direct current potential difference (PD) has been developed for use in these harsh conditions. A good correlation between PD signal and crack area has been achieved. Estimations of the crack depth have been made based on fracture surface imaging, these experimentally measured crack depth propagation rates have been compared with Paris law predictions. A stress intensity factor (SIF) interaction between multiple cracks was found, where the SIF is enhanced when cracks become close. It was found that both the fatigue cycle rate and the crack shape appear to influence the SIF magnitude and the crack depth at which specimens fail, or initiate into crack propagation which is consistent with fatigue.
Keywords: SC superalloys; Crack growth; Potential difference; Corrosive environments; Stress intensity